Production of [sigma] (1385)± and [xi] (1530)0 in p–Pb collisions at √sNN=5.02 TeV - Adamová, Dagmar; Angelov, Venelin; Arslandok, Mesut; Busch, Oliver; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; et al. (The European physical journal. C, Particles and fields, 2017)
The transverse momentum distributions of the strange and double-strange hyperon resonances (Σ(1385)±Σ(1385)±Σ (1385)^{± }, Ξ(1530)0Ξ(1530)0Ξ (1530)^{0}) produced in p-Pb collisions at sNN−−−√=5.02sNN=5.02\sqrt{s_{NN}}= 5.02 TeV were measured in the rapidity range −0.5<yCMS<0−0.5<yCMS<0-0.5< y_CMS<0 for event classes corresponding to different charged-particle multiplicity densities, ⟨⟨\langle dNchNchN_{ch}/dηlab⟩ηlab⟩η _{lab}\rangle . The mean transverse momentum values are presented as a function of ⟨⟨\langle dNchNchN_{ch}/dηlab⟩ηlab⟩η _{lab}\rangle , as well as a function of the particle masses and compared with previous results on hyperon production. The integrated yield ratios of excited to ground-state hyperons are constant as a function of ⟨⟨\langle dNchNchN_{ch}/dηlab⟩ηlab⟩η _{lab}\rangle . The equivalent ratios to pions exhibit an increase with ⟨⟨\langle dNchNchN_{ch}/dηlab⟩ηlab⟩η _{lab}\rangle , depending on their strangeness content.